Distúrbios de memória em pacientes epilépticos - Stella, Florindo [UNESP] (FapUNIFESP (SciELO), 1999)
The author studied the mnemonic activity from epileptic patients with complex partial seizures (CPS), with the aims: 1) to identify memory disorders; and 2) to compare the patients' with the controls' results. Fifty adult patients and 20 subjects without neuropsychiatric disorders were studied. The methods consisted in: 1) investigation of the mnemonic activity through the Wechsler Memory Test (subtests: Storage and Recall, Recent Memory, and Immediate Memory); 2) comparison among the results of both groups; association from mnemonic activity with brain SPECT. In the three subtests, the patients showed cognitive performance significantly lower than the controls (p <0,05). It was found association from reduced blood flow, mainly in left temporal region, with memory impairment of the three subtetsts. The conclusion was that the CPS are associated to memory impairment.
Memory disorders in epileptic patients
Keywords: Memory disorders; Neuropsychological evaluation; Temporal lobe epilepsy; adolescent; adult; cognition; female; human; male; memory disorder; middle aged; neuropsychological test; pathophysiology; temporal lobe epilepsy; Adolescent; Adult; Cognition; Epilepsy, Complex Partial; Epilepsy, Temporal Lobe; Female; Humans; Male; Memory Disorders; Middle Aged; Neuropsychological Tests